2023
DOI: 10.3390/vetsci10050352
|View full text |Cite
|
Sign up to set email alerts
|

Current Situation of Bacterial Infections and Antimicrobial Resistance Profiles in Pet Rabbits in Spain

Abstract: Research on antimicrobial resistance (AMR) in pet rabbits is very scarce. The aim of this study was to provide an overview of the current state of AMR in rabbits attended to in veterinary clinics distributed in Spain. Records of 3596 microbiological results of clinical cases submitted from 2010 to 2021 were analyzed. Staphylococcus spp. (15.8%), Pseudomonas spp. (12.7%), Pasteurella spp. (10%), Bordetella spp. (9.6%) and Streptococcus spp. (6.8%) were the most frequently diagnosed agents. Enterobacteriaceae, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The results showed 85% AMR and 82.6% MDR, in line with other studies carried out in other Spanish regions [14,15]. These percentages are alarming, as the population of small exotic mammals is continuously growing, and in close contact with their owners, thus presenting a new challenge for authorities in the legislation of new regulations to monitor AMR and MDR in this population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results showed 85% AMR and 82.6% MDR, in line with other studies carried out in other Spanish regions [14,15]. These percentages are alarming, as the population of small exotic mammals is continuously growing, and in close contact with their owners, thus presenting a new challenge for authorities in the legislation of new regulations to monitor AMR and MDR in this population.…”
Section: Discussionsupporting
confidence: 87%
“…However, NTCAs are still not included in monitoring and surveillance programmes, resulting in a lack of information addressing the epidemiologic situation of AMR in small mammals as new companion animals, and the potential for transmission of AMR genes and zoonotic pathogens to humans through the home environment they share [14,15]. Therefore, the objective of this pilot study was to assess the prevalence of commensal E. coli and whether the study population carried Salmonella, along with its AMR and MDR patterns, in small mammals from the Valencia region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is worth mentioning that no E. coli strain demonstrated resistance to PMB, which may be associated with less frequent medication. Although oral administration of ampicillin and amoxicillin/clavulanate may pose a risk of antibiotic-associated dysbiosis in certain rabbit populations ( 5 ), parenteral administration is still recommended for susceptible pathogens ( 18 , 20 ). Moreover, antibiotics from the penicillin family appear to be more readily available for veterinary use in local rabbit farming practices, which may also influence the choice of antibiotic prescription and the prevalence of relevant antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Limited epidemiological studies have reported the presence of antibiotic-resistant E. coli and Enterococcus spp. isolates in domestic or wild rabbit populations ( 18 21 ), exhibiting diverse AMR spectrums and distinctive ARG distribution across different geographical areas. However, there is a lack of knowledge regarding updated epidemiological data in Chengdu City, which is one of largest markets for meat-rabbit production and consumption in Southwest China.…”
Section: Introductionmentioning
confidence: 99%